Analytical Study of Hadiths about Women as Source of Slander - Mayada, Wafiq; Munandar, Munandar (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The word slander is often spoken in society in everyday life, namely defamation. But in this study, the word slander in question is a trial for women and men. It is said in a hadith of the Prophet Muhammad.